ZnAl LDH-based Derivative Materials as Photocatalysts: Synthesis, Characterization, and Catalytic Performance in Tetracycline Degradation - Rohmatullaili; Ahmad, Nur; Erviana, Desti; Zultriana; Savira, Dila; Mohadi, Risfidian; Lesbani, Aldes (Science and Technology Indonesia, 2024)
Layered Double Hydroxide (LDH)-derived materials exhibited different characteristics from LDH precursors. The conversion of ZnAl LDH into its derivative material has been carried out to find the best catalyst for TC degradation. ZnAl (LDH)-based catalysts in this study have been effectively synthesized using coprecipitation, calcination, and restacking procedures. ZnAl Layered Double Oxide (LDO) is derived from the calcination of ZnAl LDH at 500°C. ZnAl LDH was also modified by adding Garcinia mangostana pericarp extract (GME). XRD, FT-IR, UV-DRS, and SEM-EDX were used to investigate the synthesized catalyst. ZnAl LDH exhibited the typical LDH FT-IR spectra, whereas ZnAl LDO showed metal oxide-like spectra, and the ZnAl-GME composite displayed the combination spectra of precursor material. The ZnAl LDH XRD diffraction pattern exhibited the attributes of a layered material, whereas the other three catalysts did not. Calcination destroyed the layered structure of ZnAl LDH, whereas the addition of GME to LDH and LDO generated a single-layered composite. The modified ZnAl-GME composite showed a decrease in both particle size and bandgap energy. At an ideal pH of 5, the synthesized catalyst was used in a batch system photodegradation of 5 mg/L Tetracycline (TC), employing solar light irradiation. ZnAl LDO holds the most significant catalytic activity and structural stability through the fifth regeneration cycle, degraded TC up to 100% in 90 minutes.